Gestão do processo de projeto em escritórios de arquitetura: uma ferramenta tecnológica para auxílio na obtenção da certificação ambiental AQUA em edifícios comerciais - Lipori, Plantina Dias Fernandes (2013)
This dissertation is focused on the development of a tool to assist obtaining environmental certification for commercial buildings. A commercial building project involves many areas of knowledge, professionals with various areas of expertise and the desires of the customer. The environmental certification process intends to achieve environmental performance of an enterprise through prioritization and hierarchization of environmental goals defined in the beginning of the project and monitored until its end. There are various types of environmental certification, such as Leadership in Energy & Environmental Design (LEED), and “Alta Qualidade Ambiental” (AQUA). For this dissertation, AQUA was adopted,,since it is adapted to Brazilian reality, climate and laws. The tool developed here, FGPCA (“Ferramenta de Gestão do Processo de Certificação AQUA”), has the main objective of assisting AQUA certification for commercial buildings projects. It was built using the Eclipse Process Framework Composer (EPF) software. The tool was assessed by four companies, three of which, a sustainability consulting and two architecture offices, did the final test. This assessment detected positive points as well as points for improvement, which have been implemented. The three companies were unanimous to affirm that the tool can contribute to AQUA certification.